2021
DOI: 10.7554/elife.65482
|View full text |Cite
|
Sign up to set email alerts
|

Scaled, high fidelity electrophysiological, morphological, and transcriptomic cell characterization

Abstract: The Patch-seq approach is a powerful variation of the patch-clamp technique that allows for the combined electrophysiological, morphological, and transcriptomic characterization of individual neurons. To generate Patch-seq datasets at scale, we identified and refined key factors that contribute to the efficient collection of high-quality data. We developed patch-clamp electrophysiology software with analysis functions specifically designed to automate acquisition with online quality control. We recognized the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 67 publications
(168 reference statements)
0
66
0
Order By: Relevance
“…S3B). We performed experiments using the Patch-seq method ( 39 ) and further confirmed that cells that transcriptionally mapped to the Sst subclass do form connections with each other (five connections were found of 66 probed; fig. S3C).…”
Section: Resultsmentioning
confidence: 76%
“…S3B). We performed experiments using the Patch-seq method ( 39 ) and further confirmed that cells that transcriptionally mapped to the Sst subclass do form connections with each other (five connections were found of 66 probed; fig. S3C).…”
Section: Resultsmentioning
confidence: 76%
“…Since post-hoc HCR on MPC experiments is such a low-throughput method, we took advantage of a larger existing human single cell Patch-seq datasets to develop a quantitative classifier to predict interneuron subclass identity on our larger MPC dataset. This reference dataset comprised a set of Patch-seq experiments in slice culture that targeted AAV-DLX2.0-SYFP2 labeled neurons (Berg et al, 2021, Lee et al, 2021; see Methods ), from which the cells were robustly defined based on transcriptomic analysis following electrophysiological characterization, nucleus extraction and RNA sequencing. Such a classifier strategy was possible because intrinsic membrane properties of each cell were measured in our connectivity assays with MPC recordings, including subthreshold step hyperpolarization and depolarization from −70 mV holding potential and suprathreshold step depolarization ( Figure 3d,e,f,g , and Figure 6c ).…”
Section: Resultsmentioning
confidence: 99%
“…Paired transcriptomics and proteomics investigate the molecular content of cortical neurons ( Poulopoulos et al, 2019 ). Recent approaches allow combined electrophysiological, morphological, and transcriptomic characterization of individual neurons ( Gouwens et al, 2020 ; Kalmbach et al, 2021 ; Lee B. R. et al, 2021 ). While early morphological classifications were considered outdated, cell morphology defines circuit function; axon appositions influence wiring and elaborate glia ramifications drive synapse ensheathment and function ( Chung et al, 2015 ).…”
Section: Mapping Neural Cell Types: From Single Criteria Toward a Mul...mentioning
confidence: 99%